Clean my land: American Indians, tribal sovereignty, and the Environmental Protection Agency - Nolan, Raymond Anthony (Kansas State University, 2015)
This dissertation is a case study of the Isleta Pueblos of central New Mexico, the Quapaw tribe of northeast Oklahoma, and the Osage Nation of northcentral Oklahoma, and their relationship with the federal government, and specifically the Environmental Protection Agency. As one of the youngest federal agencies, operating during the Self-Determination Era, it seems the EPA would be open to new approaches in federal Indian policy. In reality, the EPA has not reacted much differently than any other historical agency of the federal government. The EPA has rarely recognized the ability of Indians to take care of their own environmental problems. The EPA’s unwillingness to recognize tribal sovereignty was no where clearer than in 2005, when Republican Senator James Inhof of Oklahoma added a rider to his transportation bill that made it illegal in Oklahoma for tribes to gain primary control over their environmental protection programs without first negotiating with, and gaining permission of, the state government of Oklahoma. The rider was an erosion of the federal trust relationship with American Indian tribes (as tribes do not need to heed state laws over federal laws) and an attack on native ability to judge tribal affairs. Oklahoma’s tribes, and Indian leaders from around the nation, worked to get the new law overturned, but the EPA decided to help tribes work within the confines of the new law. Despite the EPA’s stance on the new law, the tribes continued to try to fight back, as they had in the past when challenged by paternalistic federal policy. The EPA treated the Quapaws and Isletas in a similar fashion. Thus, the thesis of this study is that the EPA failed to respect the abilities of American Indian nations, as did federal agencies of years before, to manage their own affairs. Historians have largely neglected the role the EPA has played in recent Indian history and are just now beginning to document how deliberate efforts at self-determination have been employed by tribes for centuries in America.
Keywords: American Indians; Sovereignty; Environmental Protection Agency; American History (0337); Native American Studies (0740)